Growth performance, carcass characteristics and meat composition of Milanino chickens fed on diets with different protein concentrations. Issue 4 (3rd July 2016) - Mosca, F.; Kuster, C. A.; Stella, S.; Farina, G.; Madeddu, M.; Zaniboni, L.; Cerolini, S.
Abstract: Milanino is a heavy Italian chicken breed included in a conservation project of the University of Milan and is an important genetic resource for alternative production systems. This research was aimed to study the effect of the dietary protein concentration on growth, slaughter performance and meat composition in free-range reared Milanino chickens. A total of 120 Milanino chickens were fed on different protein concentrations (HP = 20% CP and LP = 16% CP), reared according to a free-range system and slaughtered at 150 and 180 d of age. Growth, slaughter performance and meat (breast and thigh) composition were recorded. The protein concentration of the diet did not affect the overall Milanino mean body weight recorded in the straight-run group in the whole rearing period. However, the growth rate within sex was significantly different between the dietary treatments: heavier females were found in the HP group from 125 d onwards, while no differences were recorded in male body weights. The protein concentration of the diet did not affect carcass weight data or meat composition. The present results suggest the use of a low-protein diet for rearing straight-run Milanino chickens for long rearing periods. However, in females, a high-protein diet is recommended from 125 d of age onwards.